Bifunctional Magnetic Luminescent Particles Based on Iron Oxide Nanoparticles Grafted with a Europium Silylated Bypiridine Tris(β‐diketonate) Complex. Issue 18 (11th November 2016) - Silva, Robson R.; Duarte, Adriana P.; Sábio, Rafael M.; Caiut, José M. A.; Gressier, Marie; Menu, Marie‐Joëlle; Franco, Adolfo; Ribeiro, Sidney J. L.
Abstract: A new highly magnetic‐luminescent nanocomposites has been synthesized by grafting luminescent europium complex comprising tris(b‐diketone) and bypridine ligand modified with a silylil function group (Eu[(TTA)3 (Bpy‐Si)] complex) on the surface of superparamagnetic iron oxide nanoparticles with 11 nm in size coated with a thin silica outer layer. The γ‐Fe2 O3 /SiO2 nanoparticles were fully characterized by ATR‐FTIR, FE‐SEM, HR‐TEM and magnetic measurements to confirm the structure of nanocomposite and the superparamagnetic behavior. Grafting with europium silylated bypiridine tris(β‐diketonate) complex on nanoparticles surface was achieved by covalent bonding through triethoxysilyl groups which allows high concentration of the luminescent species. The resulting nanocomposite display superparamagnetic profile and the indirect excitation in the ultraviolet region outcomes high red luminescence intensity (at 613 nm) with narrow characteristic emission lines of Eu(III) and emission lifetime in the millisecond range. The nanocomposite is potentially useful for applications as biolabelling, imaging, bio‐separation and bioassays. Abstract : Bifunctional magnetic‐luminescent particles were achieved by covalent grafting of [Eu(2‐thenoyl‐trifluoroacetone)3‐(4‐methyl‐4′‐(methylaminopropylalkoxysilyl)‐2, 2′‐dipyridine], silylated Eu[(TTA)3 (Bpy‐Si)] complex, on the surface of superparamagnetic iron oxide nanoparticles coated with a thin layer of silica. The particles exhibited high red fluorescence and superparamagnetic profile at room temperature, thus extending their potential applications in biophotonics and magnetic separation.